Quantitative and Qualitative Evaluation of Linguistic Input Support to a Prelingually Deaf Child With Cued Speech: A Case Study - Torres, Santiago; Moreno-Torres, Ignacio; Santana, Rafael (Journal of deaf studies and deaf education, 2006)
This paper studies the linguistic input attended by a deaf child exposed to cued speech (CS) in the final part of her prelinguistic period (18-24 months). Subjects are the child, her mother, and her therapist. Analyses have provided data about the quantity of input directed to the child (oral input, more than 1,000 words per half-an-hour session; cued ratio, more than 60% of oral input; and attended ratio, more than 55% of oral input), its linguistic quality (lexical variety, grammatical complexity, etc.), and other properties of interaction (child attention and use of spontaneous gestures). Results show that both adults provided a rich linguistic input to the child and that the child attended most of the input that the adults cued. These results might explain the positive linguistic development of children exposed early to CS.